Ouers se rol in die oordrag van etiese en morele waardes - Larney, T. (Koers, 2005)
Parental role in the transmission of ethical and moral values The primary focus of this article is to describe the characteristics and nature of the process of transmitting moral and ethical values from parents to children. The transmission of values within the framework of parents and family implies a horizontal as well as a vertical dimension. The role of parents and family can, however, not be evaluated in isolation. On a horizontal level the influence of philosophical trends and traditions, psychological theories, time-determined attitudes and social conditions are thus scrutinised in order to understand reality and different perspectives on man’s position in this world. In particular structuralistic and psychoanalytic views, as well as social determinants in the transmission of values, are discussed. Parents’ task as educators is also seen from the specific perspective of parental role in the process of instruction, parents’ modelling function and the influence of world view and attitude in transmitting moral and ethical values. In conclusion the vertical dimension of value transmission is also indicated: the influence of and the way in which children internalise religious values and a sense of religiosity is thus established.